N,N′-Bis(2-aminobenzyl)ethane-1,2-diaminium dinitrate - Garza Rodríguez, Luis Ángel; Elizondo Martínez, Perla; Bernès, Sylvain; Nájera Martínez, Blanca; Pérez Rodríguez, Nancy (Wiley-Blackwell, 2013)
In the title salt, C16H24N42+2NO3, both the cation and anion are placed in general positions, although the cation displays non-crystallographic inversion symmetry, with the aliphatic chain extended in an all-trans conformation. The benzene rings are almost parallel, with a dihedral angle between their mean planes of 3.3 (6). The nitrate ions are placed in the vicinity of the protonated amine groups, forming efficient N—HO inter-ion hydrogen bonds. Each nitrate ion in the asymmetric unit bridges two symmetry-related cations, forming an R44 (18) ring, a common motif in organic ammonium nitrate salts. This results in the formation of chains along [010] with alternating cations and anions. The neutral amine groups are involved in slightly weaker N—HO hydrogen bonds with the nitrate O atoms, and there are also a number of C—HO hydrogen bonds present. The resulting supramolecular structure is based on a two-dimensional network extending in the ab plane.